The Integrative Construction Model: A Strategic Management Approach to Religious Moderation in Indonesian Islamic Boarding Schools - Syabuddin Syabuddin; Muhammad Muhammad; Sakdiah Sakdiah; Fithriani Fithriani; Muhammad Furqan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Indonesia, as a country with religious and cultural diversity, faces serious challenges in the form of the growth of radicalism, which has the potential to disrupt social cohesion. An Islamic education management strategy is needed to foster religious moderation in Islamic boarding schools. This study aims to develop a model for managing religious moderation among Islamic boarding school students in Indonesia, emphasizing the role of Islamic boarding schools as strategic Islamic educational institutions. The research was conducted at four selected Islamic boarding schools: SPEAM Pasuruan, Ma'had Dalwa, Pesantren At-Taqwa, and Dayah Darul Abrar. Primary data were obtained through observation, interviews, and documentation, while secondary data were sourced from relevant literature. The data were then analyzed using triangulation, data reduction, data presentation, and conclusion drawing. The results of the study show three main findings: first, ustadz/ustadzah have an integrated perspective on religious moderation by emphasizing national commitment, tolerance, anti-violence, and accommodation of local culture; second, religious moderation is fostered through an integrative managerial approach in planning, organizing, implementing intracurricular and extracurricular activities, and enforcing pesantren rules; third, the resulting fosterage model is an integrated construct that integrates the dimensions of values, curriculum, student activities, and institutional governance. In conclusion, this study confirms that pesantren management grounded in an integrated perspective and an integrative construction model provides a strategic framework for institutionalizing religious moderation among students. Beyond its contribution to Islamic education management, this model offers transferable insights for religious and faith-based educational institutions worldwide, particularly in pluralistic societies confronting radicalization, intolerance, and social fragmentation.